Fibre Extraction from Oleaginous Flax for Technical Textile Applications: Influence of Pre-processing parameters on Fibre Extraction Yield, Size Distribution and Mechanical Properties. (2017) - Ouagne, P.; Barthod-Malat, B.; Evon, Ph.; Labonne, L.; Placet, V.
Abstract: Cultivated primarily for its seeds, oleaginous flax could also be valued for the different fractions that can be extracted from the straw. However, as the straws are not harvested with the same technique and care than for the textile flax, the classical scutching technique cannot be used. As a consequence, an "all fibre" device was used to perform the separation of the different constituents of the oleaginous flax straws. The different fractions were quantified for two retting levels and for two degrees of rewetting of the stems. The physical and mechanical properties of fibres were then evaluated. It appears that the relative amount of fibres extracted from oleaginous flax straw is comparable to the one from textile flax (i.e. 40% of the stem dry mass), and their tensile properties are situated in the lower part of the textile flax range. This work shows that the individual fibre length of oleaginous flax (between 3 and 6 cm) is comparable to that of the scutched textile flax fibres. This makes them suitable for the production of carded aligned fibre yarns for technical reinforcement textiles (e.g. composites or geotextiles). These results demonstrate the interest and the potential added value of harvesting the stems for technical fibre applications.